2021
DOI: 10.3390/cancers13194898
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis in Multiple Myeloma and Primary Plasma Cell Leukemia with t(11;14) Reveals Different Expression Patterns with Biological Implications in Venetoclax Sensitivity

Abstract: Mechanisms underlying the pathophysiology of primary Plasma Cell Leukemia (pPCL) and intramedullary multiple myeloma (MM) need to be further elucidated, being potentially relevant for improving therapeutic approaches. In such a context, the MM and pPCL subgroups characterized by t(11;14) deserve a focused investigation, as the presence of the translocation is mainly associated with sensitivity to venetoclax. Herein, we investigated a proprietary cohort of MM and pPCL patients, focusing on the transcriptional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…The presence of t(11;14) is traditionally regarded as a standard risk marker in MM correlating with a better outcome, though there is new evidence that may refute these stratification models [ 35 ]. It is becoming clear that t(11;14) MM is a heterogeneous disease [ 36 ] and novel findings show that t(11;14)-positive pPCL and MM have a different genetic and transcriptional background [ 37 , 38 ]. The application of two different t(11;14) probes in our series has revealed an atypical breakpoint in the 11q13 region in almost half of pPCL patients (contrarily to 13% in NDMM), providing evidence for different genetic loci and novel candidate genes that may be implicated in the appearance of the leukemic phenotype ( Supplementary Table S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of t(11;14) is traditionally regarded as a standard risk marker in MM correlating with a better outcome, though there is new evidence that may refute these stratification models [ 35 ]. It is becoming clear that t(11;14) MM is a heterogeneous disease [ 36 ] and novel findings show that t(11;14)-positive pPCL and MM have a different genetic and transcriptional background [ 37 , 38 ]. The application of two different t(11;14) probes in our series has revealed an atypical breakpoint in the 11q13 region in almost half of pPCL patients (contrarily to 13% in NDMM), providing evidence for different genetic loci and novel candidate genes that may be implicated in the appearance of the leukemic phenotype ( Supplementary Table S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, 26 articles that met the criteria were included in the final analysis. 14 , 17 , 18 , 23 , 24 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 …”
Section: Resultsmentioning
confidence: 99%
“…The included studies were then screened by title and abstract, followed by a full‐text review. Ultimately, 26 articles that met the criteria were included in the final analysis 14,17,18,23,24,33–53 …”
Section: Resultsmentioning
confidence: 99%
“…These results could help identifying patients who will respond to treatment with venetoclax. Recently, Todoerti et al ( 122 ) showed difference in expression pattern in BCL2 gene family members between MM cells with t(11:14) compared with MM cells without translocation. There is a need to determine potential predictive biomarkers for venetoclax -sensitive samples.…”
Section: Venetoclax Sensitivity In MMmentioning
confidence: 99%